1999
DOI: 10.1148/radiology.211.2.r99ma40571
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Shape: Automatic Measurement with Active Shape Models

Abstract: The shape and appearance of the spine on lateral dual x-ray absorptiometry scans were statistically modeled. To measure vertebral shape accurately, rapidly, and automatically with a computer, this trained model was matched to findings on previously unseen scans. The technique obtained entire shape information, was faster than manual analysis, and was as accurate as human observers in the measurement of vertebral shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 17 publications
1
76
0
Order By: Relevance
“…The images are assigned a score for each mode describing how many standard deviations they lie from the mean of all the images. The model may also be used to locate and characterise similar objects in new images (11)(12). The purpose of the current study was to create a shape model of the lumbar spine in the sagittal plane to characterize the lordosis and to compare the reliability and precision of the model with that of conventional lordosis measurements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The images are assigned a score for each mode describing how many standard deviations they lie from the mean of all the images. The model may also be used to locate and characterise similar objects in new images (11)(12). The purpose of the current study was to create a shape model of the lumbar spine in the sagittal plane to characterize the lordosis and to compare the reliability and precision of the model with that of conventional lordosis measurements.…”
mentioning
confidence: 99%
“…Although the main focus of our study was to characterise shape, a trained active shape model may be used to automatically locate an object in an image (11)(12). This would be particularly beneficial for analysing a time series of images, such as obtained using…”
mentioning
confidence: 99%
“…The approach is broadly applicable since, for example, segmentation of overlapping objects is almost inevitable in medical applications (e.g. [11]). Depending on the actual application, different likelihood functions might have to be adopted for example to account for differing imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Zamora et al reported success rates of 50% with average errors below 6.4 mm in active shape model (ASM) segmentation of lumbar vertebrae in spine radiographs [20]. Smyth et al performed ASM segmentation of vertebrae in dual energy X ray absorptiometry (DXA) images [16] and obtained success rates of 94 -98%, with errors in the order of 1 mm for healthy vertebra and success rates of 85 -98% with errors in the order of 2 mm for fractured vertebrae. Scott et al reported successful convergence of a modified active appearance model (AAM) in 92% of DXA scans of healthy spines with an average error of ca.…”
Section: Discussionmentioning
confidence: 99%
“…Linear models of object appearance were shown to fail in many medical image segmentation tasks [18,9,4,14]. Another drawback of current deformable model approaches it that they require initialization near the final solution, and thus need manual intervention [9,16] or automatic object recognition [5,20].…”
Section: Introductionmentioning
confidence: 99%